Ecological Variation among Natural Populations of Terminalia chebula Retz. in District Kangra, Himachal Pradesh - Sharma, Dushyant; Thakur, Sanjeev (International Journal of Bio-resource and Stress Management, 2023)
The present study was confined to three natural populations of Terminalia chebula Retz. distributed in district Kangra of Himachal Pradesh. Natural populations of Terminalia chebula Retz. In every natural population, 5 quadrats of 30×30 m2 size determined by species area curve method were randomly laid to study tree species. In each quadrat, a sub-quadrat of 5×5 m2 size for study of shrubs was selected. Among trees, Terminalia chebula was dominant tree species in Rakkar with IVI of 78.49, while Chir pine showed dominance in Praur and Bachhwain, with IVI of 142.38 and 133.01, respectively. Among shrubs Lantana camara was dominant species in Praur having IVI ( 96.37) , Carrisa opaca in Rakkar (IVI, 77.38) and Myrcine africana in Bachhwain (IVI,107.07). Population wise species diversity in trees ranged from 1.54 to 2.01, species dominance from 0.71 to 0.84, species richness 1.21 from to 1.88 and equitability from 0.75 to 0.87. Species diversity in shrubs ranged from 1.25 to 1.64, species dominance from 0.70 to 0.83, species richness from 0.76 to 1.68 and equitability from 0.91 to 0.92. The present study showed presence of mature and over mature trees of Terminalia chebula in its natural population and absence of young trees and natural regeneration indicating urgency for conservation, sustainable management and supporting regeneration of Terminalia chebula by artificial means.